Power and control strategies in online video services - Vânia Gonçalves; Tom Evens; Artur Pimenta Alves; Pieter Ballon (International Telecommunications Society (ITS), 2014)
In the emerging market of online video services, new media entrants and traditional gatekeepers are making efforts to reinvent the dominant modes of video supply and consumption while fighting for market power and customer lock-in. This article studies, through a number of U.S. and European online video services, two different groups of strategies employed by stakeholders to control their gatekeeper position and build up or maintain market power. It is suggested that traditional media gatekeepers typically engage in strategic alliances and mergers and acquisitions to establish new services and build a stronger power and bargaining position towards upstream and downstream players. In addition, copyright and IPR disputes are also being used to deter online content aggregators, which depend on content producers and broadcasters' resources. Finally, online content aggregators are building strategic alliances with CE vendors in order to quickly enter a new distribution outlet, benefit from network externalities and build market position.
Keywords: 330; Online video; online television; VOD; TV Everywhere; business model; power; alliances; mergers and acquisitions